TEACHING MANAGEMENT COMPETENCE AND STUDENTS’ CLASSROOM REACTION IN NIGERIAN UNIVERSITIES - Ajadi, Olugbenga T.; Subair, Tayo S.; Abebakin, Azeez (Sokoto Educational Review, 2014)
This study investigated students’ classroom reaction to lecturers’ classroom teaching and management competence in southwestern Nigerian universities. Two research questions were raised and one hypothesis was formulated to guide the study. A 25 - item questionnaire was drawn to elicit information from respondents selected randomly from two federal universities and three state-owned universities in southwest Nigeria. The instrument was validated using the test-retest method. The coefficient of reliability was 0.69. Both descriptive and inferential statistics were used to analyse the data gathered. The results revealed that the student-lecturer relationship and lecturers’ pedagogical skills are the influencing factors igniting students ’ classroom reaction in southwestern Universities. There is a need for lecturers in Nigerian Universities to improve on their relationship and their teaching methods as these will help to reduce students’ absenteeism rate and inattentiveness in the classroom.